Impact measurement of procuremennt post review and risk mitigation: an analysis of WB funded projects in Bangladesh - Kadir, Md. Bazlul (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.